Carrington Class Solar Events and How to Recognize Them. Issue Volume 12:Issue S328(2016) (12th September 2017) - Russell, C. T.; Luhmann, J. G.; Riley, P.
Abstract: The so-called Carrington Event on September 1, 1859, is clearly the solar outburst that brought the realization to the inhabitants of Earth that weather existed in space, and that space weather was important to the rapidly developing technological infrastructure on Earth. It is important to understand not only how space weather affects our technological systems, but like the case of atmospheric weather, the possible intensity of such weather, the frequency of extreme events, and how to predict them. This paper reviews what we know about one class of extreme space weather events, the superfast arrival events, how best to compare them given our limited diagnostics in past events and even at the current time, and suggests a direction for progress in this field.